Amelioration of Heavy Metals from Contaminated Soils of Hazaribagh and Tejgaon Areas from Bangladesh Using Red Mud - Chamon, AS; Mondol, MN; Ullah, SM (Bangladesh Journal of Scientific and Industrial Research, 2010)
Pot experiments with soil from two heavy metals contaminated sites were conducted. The objective of the experiment was to test red mud as an inorganic soil amendment to reduce heavy metal uptake and to alleviate toxicity in tomato (variety- Ratan) and wheat (variety- Agrani) crops. Iron (Fe) oxides contained in red mud, a byproduct of the aluminum industry, reduced soil to plant transfer of zinc (Zn), nickel (Ni), cadmium (Cd), and chromium (Cr). In Hazaribagh soil, tomato fruit yield (dry weight) increased by 72%. Shoot length and biomass production were positively influenced by red mud containing high amounts of Fe2O3. Heavy metal uptake into tomato plants was significantly ameliorated in both soil. On Tejgaon soil the effect of red mud on wheat grain yield production was not significantly different but the ameliorative effect of red mud application was clearly observed in the wheat grain samples for Tejgaon soil. Key words: Red Mud; Wheat; Tomato; Remediation; Heavy metals DOI: 10.3329/bjsir.v44i4.4602 Bangladesh J. Sci. Ind. Res. 44(4), 479-484, 2009